Life and death of Crocosphaera sp. in the Pacific Ocean: Fine scale predator–prey dynamics - Mathilde Dugenne; Fernanda Henderikx Freitas; Samuel T. Wilson; David M. Karl; Angelicque E. White (Limnology and Oceanography, 2020)
In the North Pacific Subtropical Gyre, the daily pulse of photosynthetic carbon (C) fixation is closely balanced by losses. This concert of growth and loss is driven by a diverse assemblage of plankton, including the diazotroph Crocosphaera sp. While primary production is relatively well characterized in this ecosystem, the extent of C transfer to secondary producers is poorly constrained. Here, we use automated imaging flow cytometry and population modeling to study the coupling of C production by Crocosphaera and subsequent grazing by nanoplanktonic protists. Crocosphaera cells represent on average 30% of the nanoplankton detected by the Imaging FlowCytoBot in the surface layer of mesoscale eddies during summertime. The size spectra show a maximum in the frequency of Crocosphaera doublet cells just prior to mitotic division at midday, with an average estimated growth rate of 0.8 ± 0.5 d −1 . We also identified potential predators by fitting a Lotka–Volterra model to plankton time series observations. Significant predators include the dinoflagellates Protoperidinium and Dinophysis as well as the ciliate Strombidium , which were all imaged with Crocosphaera in food vacuoles. The estimated C demand of the main grazers fluctuated between 25% and 250% of Crocosphaera new production in an anticyclonic eddy where we observed the onset of a Crocosphaera ‐driven bloom. Heterotrophic Protoperidinium drove most of the estimated C demand, with grazing rates nearly equivalent to Crocosphaera growth rates (0.6 ± 0.4 d −1 on average), but saturating at high prey concentrations. Our novel results demonstrate tight coupling between specific protistan predators and a diazotrophic prey.